Analisis Kerawanan Longsor Berbasis Pemetaan Geomorfologi di Manggarai Timur - Kambri, Aurelia Fermina; Saitakela, Mardhalia (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Landslide Susceptibility Analysis Using Geomorphological Mapping Approach in East Manggarai Region. Technology (IT), particularly Geographic Information Systems (GIS), plays a significant role in supporting the management of natural disasters such as landslides. East Manggarai has geographical conditions that are highly vulnerable to landslides, with topography dominated by steep hills and sharp slopes. To address this issue, it is necessary to analyze landslide susceptibility levels in the East Manggarai region using a geomorphological mapping approach through Geographic Information Systems (GIS). The mapping provides important contributions to the government in spatial planning, disaster prevention, and landslide risk mitigation. Landslide susceptibility maps and data will be published through an interactive website, facilitating information access for communities and stakeholders. This is expected to help communities identify areas prone to landslides and predict potential landslide occurrences.